Conditional and Overall Disease-Specific Survival in Patients With Paranasal Sinus and Nasal Cavity Cancer: Improved Outcomes in the Endoscopic Era. Issue 1 (January 2022) - Sharma, Rahul K.; Irace, Alexandria L.; Schlosser, Rodney J.; Overdevest, Jonathan B.; Rowan, Nicholas R.; Troob, Scott H.; Gudis, David A.
Background: The management of paranasal sinus and nasal cavity malignancies has evolved significantly with the development of advanced endoscopic techniques and improvements in adjuvant therapy. We sought to characterize both disease-specific survival (DSS) and 5-year conditional disease-specific survival (CDSS, the change in life expectancy with increasing survivorship) for sinus malignancies diagnosed before and after the year 2000. Methods: Patients diagnosed with sinus and nasal cavity cancer between 1973-2015 were extracted from the Surveillance, Epidemiology, End Results (SEER) registry. Kaplan-Meier analysis for DSS was stratified by year of diagnosis before and after 2000. Cox-proportional hazards models of DSS controlling for stage, age, and year of diagnosis were generated. CDSS was calculated using Cox-regression models stratified by stage. Results: We analyzed 10, 535 patients. Diagnosis after the year 2000 was independently associated with improved DSS (HR:0.81, 95% CI: 0.75-0.87, P < .001) after controlling for age and stage. After stratifying by stage, diagnosis after year 2000 was associated with improved DSS for localized (HR:0.71, 0.59-0.86, P < .001) malignancies, regional (HR: 0.86, 0.78-0.94, P = .001) and distant malignancies (HR 0.74, 0.63-0.87, P < .001). CDSS improved with increasing survivorship for all stages of sinus and nasal cavity cancer, and those diagnosed after 2000 had improved CDSS compared to those diagnosed before 2000. Descriptively, the association of year of diagnosis with CDSS diminished with increasing survivorship for localized cancers, but was consistent for other stages. Conclusion: For paranasal sinus and nasal cavity malignancies, year of diagnosis independently influences both DSS and CDSS. Improved survival is likely due to advances in both surgical and adjuvant treatments. To our knowledge, this study is the first to examine CDSS for these malignancies.